Molecular Changes in Normal Appearing White Matter in Multiple Sclerosis are Characteristic of Neuroprotective Mechanisms Against Hypoxic Insult - Graumann, Ursula (Brain Pathol, 2006)
Multiple sclerosis is a chronic inflammatory disease of the CNS leading to focal destruction of myelin, still the earliest changes that lead to lesion formation are not known. We have studied the geneexpression pattern of 12 samples of normal appearing white matter from 10 post‐mortem MS brains. Microarray analysis revealed upregulation of genes involved in maintenance of cellular homeostasis, and in neural protective mechanisms known to be induced upon ischemic preconditioning. This is best illustrated by the upregulation of the transcription factors such as HIF‐1α and associated PI3K/Akt signalling pathways, as well as the upregulation of their target genes such as VEGF receptor 1. In addition, a general neuroprotective reaction against oxidative stress is suggested. These molecular changes might reflect an adaptation of cells to the chronic progressive pathophysiology of MS. Alternatively, they might also indicate the activation of neural protective mechanisms allowing preservation of cellular and functional properties of the CNS. Our data introduce novel concepts of the molecular pathogenesis of MS with ischemic preconditioning as a major mechanism for neuroprotection. An increased understanding of the underlying mechanisms may lead to the development of new more specific treatment to protect resident cells and thus minimize progressive oligondendrocyte and axonal loss.